Оцінка сучасного вуглеводневого потенціалу гідродинамічної пастки рециркуляціного типу за допомогою геоінформаційного робота - Хтема, А.В.; Хтема, В.М. (Геоінформатика, 2015)
За допомогою фізико-геологічної інтерпретації каротажних діаграм, структурно-числового моделювання та геоінформаційної технології у камеральних умовах автоматизованим способом здійснено просторову локалізацію аномалій типу “вуглеводневий поклад” та отримано геоінформацію про місцезнаходження скупчень вуглеводнів, характер насичення, величину, структуру та достовірність їх запасів. На фоні обмеженого впливу структурного фактора на нафтогазоносність надр продемонстровано особливості процесу самоорганізації скупчень вуглеводнів. Сформовано геоінформаційний базис, потрібний для реконструкцій швидкості та прискорення процесу утворення скупчень вуглеводнів, оцінки динаміки величини запасів та уточнення можливостей використання фактора часу для досягнення значень коефіцієнта вилучення вуглеводнів понад одиницю. Створено геоінформаційний робот, який доцільно застосовувати у межах раніше розбурених ділянок для пошуків пропущених скупчень вуглеводнів, а також для визначення найвірогіднішого діапазону запасів вуглеводнів, підрахованих за різних варіантів кореляції каротажних діаграм. С помощью физико-геологической интерпретации каротажных диаграмм, структурно-числового моделирования и геоинформационной технологии в камеральных условиях автоматизированным способом осуществлена пространственная локализация аномалий типа “углеводородная залежь” и получена геоинформация о местонахождении скоплений углеводородов, характере насыщения, величине, структуре и достоверности их запасов. На фоне ограниченного влияния структурного фактора на нефтегазоносность недр продемонстрированы особенности процесса самоорганизации скоплений углеводородов. Сформирован геоинформационный базис, необходимый для реконструкций скорости и ускорения процесса образования скоплений углеводородов, оценки динамики изменений величины запасов и уточнения возможностей использования фактора времени для до-стижения значений коэффициентов извлечения углеводородов больше единицы. Создан геоинформационный робот, который целесообразно применять в пределах ранее разбуренных участков для поисков пропущенных скоплений углеводородов, а также для определения наиболее достоверного диапазона запасов углеводородов, подсчитанных при различных вариантах корреляции каротажных диаграмм. Purpose. The purpose of the article is to conduct spatial tracking of the trap type anomaly (deposit-type anomaly) by an automated data processing technique in office studies. To obtain digital and graphic information on the location of hydrocarbon accumulation, fluid content, quantity, structure and reliability of reserves.
Design/methodology/approach. Methods are used: physical and geological interpretation of well logs, structural and numerical modeling, digital geoinformational technology, which operates with new physical characteristics of geological environment, that were not observed and detected before. Also used are parameters of hydraulically continuous motion of natural fluid and estimation of geological reserves of hydrocarbons by volumetric method.
Findings. Within drilled out area, values of volumetric parameters were calculated and localized. As a result, we made hydrocarbon reserves estimation, including estimations of gas and fluid hydrocarbons separately. We defined reliability of estimated reserves and their structure (whether it is gas or fluid). We demonstrated a set of features of a self-organization process of hydrocarbon accumulation. A required data base was formed to reconstruct speed and accelerate petroleum accumulation, and to evaluate hydrocarbon reserves variations, as well as to ensure application of the time factor to get recovery factor values of over 1.0.
Practical value /implications. The geoinformation robot (geo-data robot) is recommended to use within drilled out areas with the purpose of searching and localizing oil-and-gas prospective objects which were missing. It is also useful for determining hydrocarbon reserves at various well logs correlations.